3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation. (February 2023) - Han, Lei; Shen, Liguo; Lin, Hongjun; Huang, Zhengyi; Xu, Yanchao; Li, Renjie; Li, Bisheng; Chen, Cheng; Yu, Wei; Teng, Jiaheng
Abstract: The oily water treatment is becoming one of the hottest topics due to that increase of offshore oil transportation and the various accident oil leakages. In this study, a functional TiO2 -ABS composite membrane was generated through the three-dimensional (3D) printing strategy for the first time and was conducted to simulated oily water treatment. The TiO2 -ABS composite membrane demonstrated a significant promotion in hydrophilicity and oleophobicity which were evidenced by the water contact angle of 14.8° and the underwater oil contact angle of 144.7°, respectively. The optimal modified membrane had both exceedingly high flux (1.8 × 10 5 L m −2 ·h −1 ) and oil rejection rate (99.5%). Moreover, the results of filtration cycles of 10 days and extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory demonstrated that the modified membranes took possession of excellent stability and antifouling property. What was more, the TiO2 -ABS composite membrane revealed over 99% rejection to all five types of oil/water systems. The interestingly experimental results indicated that the prepared membrane possessed a broad development trend and application prospect in the field of oily water treatment. Graphical abstract: Image 1 Highlights: A novel TiO2 -ABS composite membrane was firstly developed by a 3D printing technology. TiO2 -ABS composite membrane displayed water contact angle of 14.8° and underwater oil contact angle of 144.7°. TiO2 -ABS composite membrane possessed a flux of 1.8 × 10 5 L m −2 ·m −1 and rejection of 99.5%. TiO2 -ABS composite membrane revealed over 99% rejection to all five types of oil/water systems.